ISLAMIC ETHICAL INVESTMENT PADA INVESTASI REAL ASSET - Rahmah, Nur; Misbah, Irwan (STAI BHAKTI PERSADA BANDUNG, 2019)
Real asset investment is the purchase of productive assets to return profits. The motivational tendency to invest has shifted from financial satisfaction to spiritual satisfaction that considers ethics. This paper aims to explain the concept of Islamic ethical investment in real assets investment. The Islamic ethical investment concept in real asset investment uses two processes, namely screening and filtering. The screening process is filter assets, which is against sharia by making shirkah contracts, mudharabah contracts, ijarah contracts, kafalah contracts, wakalah contracts. The next process is filtering by charity, picked up to zakat from the return on investment in real assets. This research offers a concept for real asset investment that is descriptive in nature, and has not been studied in the field. It is hoped that further research will develop this concept in field research.